Experience in Using Antiviral Agents for the Treatment of Novel Coronavirus Infection (COVID-19) in Kyrgyzstan - A. A. Zurdinova; A. Z. Kutmanova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2021)
The national clinical guidelines for the treatment of novel coronavirus infection (COVID-19) are the main source of information and the reference point for clinical decision-making by healthcare professionals in the Kyrgyz Republic. The recommendations presented in these documents are largely based on data from real clinical practice, but the efficacy and safety of a number of antiviral agents, the indications for which have been expanded to include COVID-19 treatment, remain unclear.The aim of the study was to conduct a retrospective pharmacoepidemiological analysis of lopinavir+ritonavir use in hospitals in the Kyrgyz Republic for the treatment of COVID-19 during the period from March until April 2020.Materials and methods: the paper describes a retrospective study of 145 medical records of patients with confirmed COVID-19 who were hospitalized in infectious disease departments/hospitals of the Kyrgyz Republic. Statistical processing was performed using Microsoft Excel 2017.Results: between 16 March 2020 and 25 April 2020, 145 patients were prescribed lopinavir+ritonavir at a dose of 200 mg + 50 mg, 2 tablets twice a day-in line with the dosage regimen recommended by the national guideline. The national guideline recommended the treatment duration of 10 days, while the actual treatment duration was 1-12 days (5.5 days on average) depending on the tolerability of the drug. The use of the drug was accompanied by adverse drug reactions (ADRs) in 78 patients (53.8%), and caused deterioration in the general condition of 73 of these patients (94.8%) which resulted in discontinuation of the drug. The most common ADRs were nausea, vomiting, diarrhoea, decreased appetite, yellowness of the skin, and, according to laboratory studies, an increase in serum levels of bilirubin, creatinine, glucose, aspartate aminotransferase and amylase activity. A retrospective assessment of the causal relationship probability according to the Naranjo scale showed an interrelation between the use of lopinavir+ritonavir and ADR development.Conclusions: the use of the lopinavir+ritonavir drug in COVID-19 patients led to deterioration of their general condition, which was severe in some cases. The data obtained indicate that the use of this drug for COVID-19 treatment is clinically unreasonable and irrational. Lopinavir+ritonavir was excluded from subsequent revisions of the clinical guidelines for the diagnosis and treatment of COVID-19 in the Kyrgyz Republic.